Mass production of carbon nanofibers using microwave technology - Mujawar, Mubarak; Abdullah, E.; Sahu, J.; Jayakumar, N.; Ganesan, P. (American Scientific Publishers, 2015)
Copyright © 2015 American Scientific Publishers All rights reserved.Carbon nanotubes (CNFs) were produced by gas phase single stage microwave assisted chemical vapour deposition (MA-CVD) using ferrocene as a catalyst and acetylene (C2H2) and hydrogen (H2) as precursor gases. The effect of the process parameters such as microwave power, radiation time, and gas ratio of C2H2/H2 was investigated. The CNFs were characterized using scanning and transmission electron microscopy (TEM), and by thermogravimetric analysis (TGA). Results reveal that the optimized conditions for CNF production were 1000 W reaction power, 35 min radiation time, and 0.8 gas ratio of C2H2/H2. TEM analyses revealed that the uniformly dispersed CNFs diameters ranging from 115-131 nm. The TGA analysis showed that the purity of CNF produced was 93%.